Wetlands and infectious diseases - Zimmerman Robert H. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
There is a historical association between wetlands and infectious disease that has led to the modification of wetlands to prevent disease. At the same time there has been the development of water resources projects that increase the risk of disease. The demand for more water development projects and the increased pressure to make natural wetlands economically beneficial creates the need for an ecological approach to wetland management and health assessment. The environmental and health interactions are many. There is a need to take into account the landscape, spatial boundaries, and cross-boundary interactions in water development projects as well as alternative methods to provide water for human needs. The research challenges that need to be addressed are discussed.